Hungarian military forces in Africa - past and future: Recovering lost knowledge, exploiting cultural anthropology resources, creating a comprehensive system of training and preparation - Besenyő, János (Études sur la Région Méditerranéenne, 2012)
My study reviews the operations of the Hungarian military forces in Africa not only from the perspective of international (UN, EU) peace operations but also through the experiences of those who served on the spot, as well as examine the professional requirements involved. Another aspect of my study is to find a solution to the use of cultural anthropology in the mission area, in order to save our soldier’s lives.